Afrostyrax lepidophyllus Mildbr. and Monodora myristica (Gaertn.) Dunal Extracts Decrease Doxorubicin Cytotoxicity on H9c2 Cardiomyoblasts. (22nd February 2021) - Moukette, Bruno M.; Castelão-Baptista, José P.; Ferreira, Luciana; Silva, Ana M.; Simões, Rui F.; Cabral, Célia; Pieme, Constant A.; Ngogang, Jeanne Y.; Sardão, Vilma A.; Oliveira, Paulo J.
Abstract : Ethnopharmacological Relevance . Doxorubicin (Dox) is an anthracycline antibiotic widely used in cancer treatment. Despite its antitumor efficacy, its clinical application is significantly limited because of its cardiotoxicity originated, among other factors, from pro-oxidant damage to cardiac mitochondria. Phytochemicals represent a potentially attractive strategy to mitigate Dox cardiotoxicity due to their antioxidant properties, with plant extracts used in traditional medicine often being ignored in terms of potential therapeutic uses. Aim of the Study . The present study aimed at investigating the protective effects of two native Cameroonian plants, Afrostyrax lepidophyllus Mildbr. ( A. lepidophyllus ) and Monodora myristica (Gaertn.) Dunal ( M . myristica ), against Dox-induced cytotoxicity on cultured H9c2 cardiomyoblast cells. Materials and Methods . Bark extracts of these plants (1 and 25 µ g/mL) were added 3 hours before coincubating H9c2 cardiomyoblasts with Dox (0.5 and 1 µ M) for 24 hours more. We measured cell mass and metabolic viability, mitochondrial transmembrane potential, superoxide anion content, and activity-like of caspase-3 and caspase-9 following treatment with the extracts and/or Dox. Also, selenium and vitamin C contents were measured in the plant extracts. Results . The results confirmed that Dox treatment decreased cell mass, mitochondrial membrane potential and metabolic viability, increased mitochondrial superoxide anion, and stimulated caspase-3 and caspase-9-like activities. Pretreatment of the cells with the plant extracts significantly inhibited Dox cytotoxicity, with more significant results at the higher concentration. Measurements of selenium and vitamin C in the extracts revealed higher concentration of both when compared with other Cameroonian spices. Conclusion . Both extracts of A. lepidophyllus and M. myristica were effective against Dox-induced cytotoxicity, most likely due to their content in antioxidants.